2012
DOI: 10.1007/s10460-012-9391-9
|View full text |Cite
|
Sign up to set email alerts
|

Farming alone? What’s up with the “C” in community supported agriculture

Abstract: This study reconsiders the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
81
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(108 citation statements)
references
References 38 publications
10
81
1
2
Order By: Relevance
“…In line with previous studies [12,[44][45][46][47], our findings indicate that, on average, CSA members are younger, are more educated, and have higher incomes than do non-members. Furthermore, consistent with [34], our results highlight that CSA members spend more on grocery shopping and have more active lifestyles than do non-members.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…In line with previous studies [12,[44][45][46][47], our findings indicate that, on average, CSA members are younger, are more educated, and have higher incomes than do non-members. Furthermore, consistent with [34], our results highlight that CSA members spend more on grocery shopping and have more active lifestyles than do non-members.…”
Section: Resultssupporting
confidence: 92%
“…A consistent theme within the CSA literature is that women constitute the majority of CSA members [5,12,[48][49][50][51]. However, in line with the results of a recent Food Demand Survey, which indicated that people who shopped at farmers markets were more likely to be male [52], males represent a larger percentage of CSA members in our sample (Table 2).…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…There is certainly evidence of this in the research, particularly in the UK case studies. Yet, as Pole and Gray (2013) and Si et al (2015) point out, ''community'' can be hard to locate, even for those who do participate in aspects of farming and gardening. This is most clearly the case in China, with many of those involved in the farms feeling isolated from the consumers, most of whom do no more than reserve their produce on-line.…”
Section: Experiencing Communitymentioning
confidence: 99%